2022
DOI: 10.1016/j.pedneo.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hyperglycemia in extremely low birth weight infants during the first 14 days

Abstract: Background: There are limited data regarding the risk factors for hyperglycemia in extremely low birth weight infants (ELBWIs). The aim of this observational study was to investigate the incidence of hyperglycemia among ELBWIs during the first 14 days of life and identify independent risk factors for hyperglycemia development. Methods: We retrospectively evaluated 55 ELBWIs (32 male infants) between January 2015 and March 2020. Hyperglycemia was diagnosed when the glucose level was 180 mg/dL. Demographic and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…Hyperglycemia most commonly affects ELBW infants in the first week of life. In previous reports, the incidence of hyperglycemia in ELBW in the neonatal period ranges from 38% to 85% [9,37,38]. The incidence of hyperglycemia in our study was 9.9%, which is significantly lower than in other similar studies [5,19].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Hyperglycemia most commonly affects ELBW infants in the first week of life. In previous reports, the incidence of hyperglycemia in ELBW in the neonatal period ranges from 38% to 85% [9,37,38]. The incidence of hyperglycemia in our study was 9.9%, which is significantly lower than in other similar studies [5,19].…”
Section: Discussioncontrasting
confidence: 72%
“…It has been associated with significant morbidity and mortality, including intraventricular hemorrhage, retinopathy of prematurity, necrotizing enterocolitis, and abnormal neurologic examination at two years of age [5][6][7][8]. Several risk factors contribute to the development of hyperglycemia in preterm infants, including gestational age, low birth weight, stress, excessive glucose administration, parenteral nutrition, and the administration of some drugs, such as corticosteroids, phenytoin, or theophylline [9][10][11]. Hypoglycemia is a very common, usually transient, metabolic disturbance in newborn infants as a result of an adjustment to the extrauterine environment.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple risk factors for and complications of NEC have been described. 10 33 34 35 36 37 38 When the associations with confirmed NEC were explored with regression models, confirmed NEC showed a stronger association with BW than previously reported with approximately 20 to 30% reduced incidence for every 100-g increment and approximately 10 to 20% for every GA week at birth. 35 Overall, confirmed NEC associated with up to 4.7 times increased risks, e.g., GI perforation, intestinal obstruction, hypotension, hypokalemia, hyponatremia, and LOS.…”
Section: Discussionmentioning
confidence: 84%
“…A study in Tokyo, Japan examined the factors affecting hyperglycaemia in ELBW in the first 14 DOL (37). That study found significant associations between hyperglycaemia and various parameters.…”
Section: Risk Factors Of Hyperglycaemia and Its Impact On Clinical Ou...mentioning
confidence: 99%
“…That study found significant associations between hyperglycaemia and various parameters. Specifically, factors such as gestational duration, birth weight, chorioamnionitis and postnatal glucocorticoid use were identified as key factors influencing the outcome (37). Additionally, maternal preeclampsia, the premature rupture of membranes and antepartum haemorrhage have also been found to be notable risk factors for hyperglycaemia (5).…”
Section: Risk Factors Of Hyperglycaemia and Its Impact On Clinical Ou...mentioning
confidence: 99%